Statistical analyasis of major industrial accidents in China from 2000 to 2020. (November 2022) - Xiang, Yue; Wang, Ziyun; Zhang, Cheng; Chen, Xingbai; Long, Enshen
Highlights: This study investigated 478 major industrial accidents in China from 2000 to 2020. Pearson correlation analysis was carried out between industrial added value and major industrial accidents. The accident characteristics and domino effect of major industrial accidents in China were analysed. Helpful information for China's risk assessment and safety management of industrial clusters was obtained. Abstract: Understanding historical accidents are essential for accident prevention. This study analysed industrial accidents' characteristics and the domino effect of 478 major industrial accidents in China from 2000 to 2020, including time, location, accident levels and types, hazardous substances involved, working situations, and accident causes. Industrial accidents are mainly distributed in the eastern coastal industrial provinces, and concentrated in March, April, July and August, more likely to occur at 9:00–11:00 and 15:00–16:00. More than 80 % of industrial accidents occurred during normal operations and maintenance & overhaul work. 41.6 % were explosions, and 32.4 % were fires. Industrial accidents mainly involved flammable liquids and gases, and 49 % were caused by violations or improper operation. The primary events of industrial domino accidents were mainly explosions. The most frequent final domino sequences were explosion → fire (23.7 %), fire → explosion (15.3 %) and leakage → explosion (15.3 %). The ratio between first-level and second-level domino effect sequences was 2.5.